Structural basis for the inhibition of HTLV-1 integration inferred from cryo-EM deltaretroviral intasome structures - Barski, Michal S.; Vanzo, Teresa; Zhao, Xue Zhi; Smith, Steven J.; Ballandras-Colas, Allison; Cronin, Nora B.; Pye, Valerie E.; Hughes, Stephen H.; Burke, Terrence R.; Cherepanov, Peter; Maertens, Goedele N. (Nature communications, 2021)
Between 10 and 20 million people worldwide are infected with the human T-cell lymphotropic virus type 1 (HTLV-1). Despite causing life-threatening pathologies there is no therapeutic regimen for this deltaretrovirus. Here, we screened a library of integrase strand transfer inhibitor (INSTI) candidates built around several chemical scaffolds to determine their effectiveness in limiting HTLV-1 infection. Naphthyridines with substituents in position 6 emerged as the most potent compounds against HTLV-1, with XZ450 having highest efficacy in vitro. Using single-particle cryo-electron microscopy we visualised XZ450 as well as the clinical HIV-1 INSTIs raltegravir and bictegravir bound to the active site of the deltaretroviral intasome. The structures reveal subtle differences in the coordination environment of the Mg 2+ ion pair involved in the interaction with the INSTIs. Our results elucidate the binding of INSTIs to the HTLV-1 intasome and support their use for pre-exposure prophylaxis and possibly future treatment of HTLV-1 infection. Human T-cell lymphotropic virus type 1 (HTLV-1) is an oncogenic deltaretrovirus. Here the authors provide structural characterization of the binding mechanism of novel integrase strand transfer inhibitor (INSTI) candidates to limit HTLV-1 infection.